THE PERCEPTION OF EFL STUDENTS ON THE DEVELOPMENT OF STUDENTS’ READING HABIT THROUGH DIGITAL MANGA - Ramadhan, Bramantara Haikal; Wulyani, Anik Nunuk; Febrianti, Yusnita (Universitas Negeri Malang, 2022)
This study aims to investigate students’ perception on their development of reading habit through English-translated digital manga. This study used a survey research design to 60 students and an additional interview to 5 students. The data collection is collected through questionnaire. Around 83% of students out of 60 students believe that reading digital manga develops their reading habit. From the result of this study, most of the participants believe that English-translated digital manga is able to develop their reading habits for it helps them to allocate a certain time to have a reading activity, and also helps them spare their leisure time to have a reading activity that they like. The digital manga is also inexpensive and provides gorgeous pictures and artstyles that motivate the students to read more. Thus, this study implies that English-translated digital manga indeed contribute to the development of reading habit for EFL students.